- Immediate complications of Nissen fundoplication - Corradi, Daniel; Estapé, Gonzalo; Delgado, Bolívar (Cirugía del Uruguay, 1986)
Retrospeclive study of a series of 90 Nissen's fundoplicalions from the point of view of the morbimortality of same, showing both are low (morbility 18% and mortality between 1 % and 5%) while also pointing out lhat in sorne complications, such as gastric perforations, said percentages are greatly increased.